From genes to genomes concepts and applications of DNA technology - Dale, Jeremy (Jeremy W.) (Wiley-Blackwell, 2012)
Rapid advances in a collection of techniques referred to as gene technology, genetic engineering, recombinant DNA technology and gene cloning have pushed molecular biology to the forefront of the biological sciences.